A protective slag binder and its application

By using sodium carboxymethyl starch, bentonite, shavedextrin, polyacrylamide, nanotitanium dioxide and calcium lignin sulfonate in the protective slag bonding agent, the problems of slow reaction rate and component segregation in continuous casting production are solved, and a more uniform reaction and lower harmful gas production are achieved.

CN119140774BActive Publication Date: 2025-04-15HENAN COAL CHEM RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411653255.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-15
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The reaction rate of existing protective slag bonding agents is slow during continuous casting, resulting in component segregation after melting of protective slag, which affects the surface quality of the casting billet and increases friction, which may lead to defects such as surface cracks. At the same time, the existing protective slag reacts sufficiently after segregation, causing harmful gases to occur.

Method used

A protective slag binding agent is used, including sodium carboxymethyl starch, bentonite, toxendrin, polyacrylamide, nanotitanium dioxide and calcium lignin sulfonate. Through the combination and interaction of these components, the segregation of the components is inhibited and the reaction rate and uniformity are improved.

Benefits of technology

It effectively suppresses the segregation of components in the protective slag, reduces the reduction of lubricant components near the crystallizer wall, reduces the risk of defects such as cracks on the surface of the casting billet, and promotes the more complete reaction of components in the protective slag, and reduces the generation of harmful gases.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of casting additives, and particularly relates to a protective slag binder and an application thereof, comprising 600-650 parts by weight of sodium carboxymethyl starch, 220-280 parts by weight of bentonite, 100-120 parts by weight of yellow dextrin, 8-11 parts by weight of polyacrylamide, 5-8 parts by weight of nano titanium dioxide, and 10-15 parts by weight of calcium lignin sulfonate. The protective slag binder can be used in the preparation of protective slag, and can inhibit the separation of components due to density differences, such as the segregation phenomenon between lighter components such as carbon and graphite and heavier components such as calcium and aluminum. At the same time, the nano titanium dioxide combined with the calcium lignin sulfonate can adjust the reaction path by participating in the reaction between the components, thereby reducing the side reaction of generating harmful gases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of casting additives, and in particular relates to a protective slag binder and application thereof. Background Art

[0002] In the foundry industry, protective slag is needed to improve the quality of molten steel casting, and a binder is needed in the preparation process of the protective slag. The binder makes the produced protective slag particles more complete and uniform, and improves the stability of the protective slag. For example, a binder disclosed in the invention patent with the authorized patent announcement number CN103600020B includes 8-15 parts by weight of sodium carboxymethyl cellulose, 10-20 parts by weight of phenolic resin, 10-20 parts by weight of polyvinyl alcohol, 20-40 parts by weight of sodium bentonite, 3-10 parts by weight of dextrin and 10-20 parts by weight of polyacrylamide, etc. The sodium carboxymethyl cellulose, phenolic resin, polyvinyl alcohol and other materials in the formula can maintain the uniformity of the distribution of the various material components of the protective slag, and improve the stable structure formed after the various materials of the protective slag are combined.

[0003] However, the existing binders can only play a bonding role. During the continuous casting production process, the protective slag produced by using this type of binder has a slow reaction rate. The melted protective slag is prone to component segregation, with calcium, aluminum, and silicon components decreasing, and carbon, graphite and other components floating up, resulting in uneven distribution of the components of the protective slag on the crystallizer wall and the surface of molten steel, affecting its performance. At the same time, it will increase the friction between the crystallizer and the ingot, which may lead to a decrease in the surface quality of the ingot and defects such as surface cracks. At the same time, the existing protective slag is prone to insufficient reaction after segregation, resulting in the generation of harmful gases. In order to avoid such a situation, a new type of protective slag binder that can improve the quality of the protective slag is needed. Summary of the invention

[0004] In view of the above problems, the present invention proposes a protective slag binder and its application, which effectively solves the problem that the protective slag produced by the binder in the prior art has a slow reaction rate, and the melted protective slag is prone to segregation, which increases the friction between the crystallizer and the ingot, resulting in a decrease in the surface quality of the ingot. At the same time, the existing protective slag is prone to insufficient reaction after segregation occurs, resulting in the generation of harmful gases.

[0005] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: a protective slag binder, comprising 600-650 parts by weight of sodium carboxymethyl starch, 220-280 parts by weight of bentonite, 100-120 parts by weight of yellow dextrin, 8-11 parts by weight of polyacrylamide, 5-8 parts by weight of nano titanium dioxide, and 10-15 parts by weight of calcium lignin sulfonate.

[0006] The protective slag binder can be applied to the preparation of protective slag.

[0007] Furthermore, the components in the protective slag include but are not limited to a combination of one or more components of calcium, aluminum, silicon, fluorite, potassium, carbon, and graphite.

[0008] Compared with the prior art, the present invention has the following beneficial effects:

[0009] The binder in the liquid protective slag of the present invention can inhibit the separation of components due to density differences, such as the segregation between lighter components such as carbon and graphite and heavier components such as calcium and aluminum. Nano-titanium dioxide and calcium lignin sulfonate can make them better mixed together, thereby reducing the reduction of lubricant components near the crystallizer wall due to segregation and reducing the risk of defects such as cracks on the surface of the ingot.

[0010] At the same time, the present invention also helps to maintain the uniform distribution of fluorite in the protective slag, making the fluxing effect more stable. By accurately controlling the composition ratio of nano-titanium dioxide and calcium lignin sulfonate in the protective slag, its melting point and solidification point can be more effectively adjusted to better match the temperature curve of the continuous casting process.

[0011] In addition, nano-titanium dioxide combined with calcium lignin sulfonate can regulate the reaction path by participating in the reaction between components and reduce the side reactions that produce harmful gases. For example, in the reaction involving fluorite, nano-titanium dioxide can make the decomposition and reaction of fluorite more orderly, reduce the uncontrolled release of fluoride, and promote a more complete reaction of the components in the protective slag, reducing the production of carbon monoxide due to incomplete reaction of carbon and graphite. DETAILED DESCRIPTION

[0012] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0013] A protective slag binder comprises 600-650 parts by weight of sodium carboxymethyl starch, 220-280 parts by weight of bentonite, 100-120 parts by weight of yellow dextrin, 8-11 parts by weight of polyacrylamide, 5-8 parts by weight of nano titanium dioxide, and 10-15 parts by weight of calcium lignin sulfonate.

[0014] In this embodiment, the protective slag binder is prepared by crushing sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano titanium dioxide and calcium lignin sulfonate and mixing them. The sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano titanium dioxide and calcium lignin sulfonate have a mesh size of ≤200 and a moisture content of ≤0.5% after crushing. The mixing method can be a planetary mixer.

[0015] In this embodiment, the mold slag binder can be applied to the preparation of mold slag.

[0016] In this embodiment, the components in the protective slag include but are not limited to a combination of one or more components of calcium, aluminum, silicon, fluorite, potassium, carbon, and graphite.

[0017] The abundant hydroxyl groups in the sodium carboxymethyl starch can form chemical bonds or hydrogen bonds with the surface of the calcium component to better wrap the calcium particles and prevent the calcium particles from agglomerating during the storage and early use of the protective slag. At the same time, under high temperature conditions, the distribution of the calcium component can be stabilized, which is conducive to the reaction of calcium and silicon, and promotes the formation of a uniform calcium silicate phase, making it easier to control the melting point and viscosity of the protective slag.

[0018] The interlayers of montmorillonite in the bentonite can adsorb calcium ions, and the bentonite with a mass ratio of 22-280 parts provides sufficient adsorption sites for calcium ions. This adsorption can adjust the activity of the calcium component in the protective slag, allowing the calcium ions to participate in the reaction at a suitable temperature stage. In addition, the bentonite can improve the plasticity of the protective slag and prevent the problem of uneven adhesion of the protective slag on the crystallizer wall that may be caused by the presence of calcium components;

[0019] The yellow dextrin can form a sticky film on the surface of calcium and aluminum particles, and the yellow dextrin and sodium carboxymethyl starch act synergistically to enhance the wrapping effect on the materials in the protective slag;

[0020] The polyacrylamide can disperse calcium and aluminum particles more stably in the mold slag through the entanglement and adsorption of its polymer chain. In the process of interaction with other components, it can avoid the sedimentation or segregation of calcium and aluminum particles due to factors such as density, thereby ensuring the uniformity of calcium in the entire mold slag system;

[0021] Nano-titanium dioxide is nano-level titanium dioxide, which has a highly active effect. It can be adsorbed on the surface of calcium particles. On the one hand, it prevents calcium particles from agglomerating. On the other hand, it can serve as a catalyst for the reaction of other components in the protective slag at high temperatures. For example, in the process of calcium and silicon reacting in the protective slag to form calcium silicate and calcium, aluminum, and silicon forming a complex phase of calcium aluminum feldspar, nano-titanium dioxide can serve as an active site for the reaction to increase the reaction rate, thereby avoiding the problems of inadequate reaction and uneven distribution caused by segregation. At the same time, the formation of a uniform complex phase of calcium aluminum feldspar is more conducive to the adsorption of inclusions in molten steel and purification of molten steel; at the same time, nano-titanium dioxide can promote the reaction of potassium and silicon. Potassium-silicon glass phase should be generated, so that the protective slag begins to melt at a lower temperature; in a high temperature environment, nano-titanium dioxide can react with carbon atoms on the surface of graphite. The titanium atoms in nano-titanium dioxide have multiple valence states. Under appropriate conditions, it can react with carbon on the surface of graphite to form a protective film containing titanium-carbon-oxygen components. This protective film can prevent oxygen from further contacting carbon atoms inside the graphite, thereby improving the antioxidant capacity of graphite. At the same time, when graphite interacts with calcium, aluminum and other components in the protective slag, the titanium-oxygen bond on the surface of nano-titanium dioxide can interact with the carbon-carbon bond of graphite and the chemical bonds of calcium and aluminum components. This interaction can reduce the activation energy of the reaction, making it easier for graphite to react with other components to generate compounds with better lubrication properties. For example, some composite compounds containing graphite, calcium, aluminum and titanium may be formed. These compounds can form a more stable and smoother lubrication film between the crystallizer wall and molten steel, and can also reduce carbon monoxide emissions formed by insufficient reactions;

[0022] The calcium lignin sulfonate itself contains calcium element, which can be used as a supplementary source of calcium or a buffer to stabilize the calcium content in the protective slag system. At the same time, the calcium lignin sulfonate can interact with the silicon component, and its sulfonic acid group can form a chemical bond or a hydrogen bond with the oxygen atom on the silicon surface, thereby promoting the reaction of silicon with calcium in the protective slag to produce calcium silicate; the role of fluorite in the protective slag is mainly to act as a flux. At high temperature, fluorite reacts with calcium lignin sulfonate to form a [Ca-calcium lignin sulfonate-F] complex through the exchange of hydrogen ions in the sulfonic acid group with fluorine ions in the fluorite. This reaction avoids the reduction of the melting point due to the increased activity of nano-titanium dioxide, and at the same time, the fluorine ions released by the fluorite during the reaction can be more evenly located in a suitable position; the sulfonic acid group can form a chemical bond or a hydrogen bond with the active site on the surface of graphite, making the graphite more stable in the protective slag. At high temperature, the calcium lignin sulfonate can adjust the activity of graphite, and cooperate with other components to enable the graphite to better play its lubrication and anti-oxidation functions;

[0023] In this embodiment, the calcium in the protective slag is calcium oxide, the aluminum is alumina, the silicon is silicon dioxide, the fluorite is calcium fluoride, the potassium is potassium carbonate, the carbon is coke powder, and the graphite is flake graphite. The mass ratio of calcium oxide, alumina, silicon dioxide, calcium fluoride, potassium carbonate, coke powder and flake graphite is 20:15:30:8:3:6:10. The protective slag is mixed with a binder and granulated to form a finished protective slag. The mass ratio of the protective slag to the binder is 75:25.

[0024] The following is a comparison through multiple groups of specific embodiments and a group of comparative examples. The viscosity and complete melting time of the protective slag are obtained by YB / T 185-2017 "Test Method for Viscosity of Continuous Casting Protective Slag" and YB / T 186-2014 "Test Method for Melting Temperature of Continuous Casting Protective Slag".

[0025] Example 1: The mass ratio of sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano-titanium dioxide and calcium lignin sulfonate in the binder is 625:255:112:9.5:5:6. After experimental testing, the melting point of the protective slag is about 1130°C, the viscosity is 0.8-1.0 Pa·s at 1300°C, and the time for the protective slag to completely melt from room temperature is 20-22 minutes;

[0026] Example 2: The mass ratio of sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano-titanium dioxide and calcium lignin sulfonate in the binder is 625:255:112:9.5:5:15. After experimental testing, the melting point of the protective slag is about 1120°C, the viscosity is 0.7-0.9 Pa·s at 1300°C, and the time for the protective slag to completely melt from room temperature is 18-20 minutes;

[0027] Example 3: The mass ratio of sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano-titanium dioxide and calcium lignin sulfonate in the binder is 625:255:112:9.5:8:15. After experimental testing, the melting point of the protective slag is about 1100°C, the viscosity is 0.6-0.8 Pa·s at 1300°C, and the time for the protective slag to completely melt from room temperature is 16-18 minutes;

[0028] Example 4: The mass ratio of sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano-titanium dioxide and calcium lignin sulfonate in the binder is 625:255:112:9.5:8:10. After experimental testing, the melting point of the protective slag is about 1110°C, the viscosity is 0.7-0.85 Pa·s at 1300°C, and the time for the protective slag to completely melt from room temperature is 19-20 minutes;

[0029] Example 5: The mass ratio of sodium carboxymethyl starch, bentonite, yellow dextrin, polyacrylamide, nano-titanium dioxide and calcium lignin sulfonate in the binder is 625:255:112:9.5:5:10. After experimental testing, the melting point of the protective slag is about 1125°C, the viscosity is 0.8-1.0 Pa·s at 1300°C, and the time for the protective slag to completely melt from room temperature is 19-20 minutes;

[0030] Comparative Example 1: The mass ratio of sodium carboxymethyl starch, bentonite, yellow dextrin and polyacrylamide in the binder is 625:255:112:9.5. After experimental testing, the melting point of the protective slag is about 1170°C, the viscosity is 1.1-1.2 Pa·s at 1300°C, and the time for the protective slag to be completely melted from room temperature is 24-27 minutes.

[0031] It can be obtained from Example 1, Example 2 and Comparative Example 1 that by adding the binder of nano titanium dioxide and calcium lignin sulfonate, the melting point and viscosity of the protective slag meet the requirements of continuous casting production.

[0032] By comparing Example 1 with Comparative Example 1, it can be seen that the addition of nano titanium dioxide and calcium lignin sulfonate can effectively reduce the melting point and complete melting time of the protective slag;

[0033] By comparing Example 1 and Example 2 with Comparative Example 1, it can be obtained that after adding nano-titanium dioxide and calcium lignin sulfonate, the viscosity of the binder is reduced in a molten state at 1300°C, which is conducive to better spreading of the protective slag in the crystallizer to form a uniform liquid slag layer, thereby effectively lubricating the contact surface between the ingot and the crystallizer wall.

[0034] Through Example 2 and Example 1, it can be obtained that by increasing the mass ratio of calcium lignin sulfonate in the binder, the time for the protective slag to be completely melted from room temperature can be effectively reduced while reducing the decrease in the melting point of the protective slag.

[0035] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A mold slag binder, characterized in that: The invention comprises 600-650 parts by weight of sodium carboxymethyl starch, 220-280 parts by weight of bentonite, 100-120 parts by weight of yellow dextrin, 8-11 parts by weight of polyacrylamide, 5-8 parts by weight of nano titanium dioxide and 10-15 parts by weight of calcium lignin sulfonate.

2. An application of the protective slag binder according to claim 1, characterized in that: The protective slag binder can be applied to the preparation of protective slag.

3. The use of the protective slag binder according to claim 2, characterized in that: The components in the protective slag include a combination of one or more components including calcium, aluminum, silicon, fluorite, potassium, carbon, and graphite.

Citation Information

Patent Citations

  • A kind of binder and preparation method thereof

    CN103600020B

  • Binder and preparation method thereof

    CN103600020A

  • Ti element control method for Ti-contained corrosion resistant alloy ingot extracting electroslag remelting slab

    CN104212977A